استخدام نماذج البرمجة الهدفية الصحيحة لمعالجة مشكلة عدم وجود حل ممكن في البرمجة الخطية : دراسة مقارنة - عربية عبد الرحمن داؤد; خالد عبدالله العلاف (PROSPECTIVE RESEARCHES, 2023)
In this paper the researchers have used the basic concepts of goal programming models to solve the problem of no feasible solution in linear programming model and in the same time to be model which is more realistic and modern to solve the problem of distributing health staff when the constraint of available staff less than the lower bound. We present many models with one goal and multiple goals that integer decision variables to treat the problem to reach the satisfactory solution as alternative of optimal solution which can not be always reached, at.